2017
DOI: 10.1111/mec.14443
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for interannual variation in genetic structure of Dungeness crab (Cancer magister) along the California Current System

Abstract: Using a combination of population- and individual-based analytical approaches, we provide a comprehensive examination of genetic connectivity of Dungeness crab (Cancer magister) along ~1,200 km of the California Current System (CCS). We sampled individuals at 33 sites in 2012 to establish a baseline of genetic diversity and hierarchal population genetic structure and then assessed interannual variability in our estimates by sampling again in 2014. Genetic diversity showed little variation among sites or across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 134 publications
0
20
0
Order By: Relevance
“…While we attempted to control for variation between individuals by collecting animals from the same location within a 2-month period, we were unable to control for prior environmental exposure or genetic background of the wild-caught animals we used. Where prior studies have found high genetic variation among individuals within one sampling site 47,48 , we suspect that both genetics and prior environmental exposure likely contributed to the high variation in metabolite abundances among individuals within treatment groups, which may have obscured the different treatment effects. Within-sample variation could be reduced by sampling from a specific tissue rather than using whole animals, however this may be challenging in early stage juvenile Dungeness crabs given their small size.…”
Section: Discussionmentioning
confidence: 90%
“…While we attempted to control for variation between individuals by collecting animals from the same location within a 2-month period, we were unable to control for prior environmental exposure or genetic background of the wild-caught animals we used. Where prior studies have found high genetic variation among individuals within one sampling site 47,48 , we suspect that both genetics and prior environmental exposure likely contributed to the high variation in metabolite abundances among individuals within treatment groups, which may have obscured the different treatment effects. Within-sample variation could be reduced by sampling from a specific tissue rather than using whole animals, however this may be challenging in early stage juvenile Dungeness crabs given their small size.…”
Section: Discussionmentioning
confidence: 90%
“…Spatially, subpopulations that are geographically proximate may exhibit greater genotypic differentiation than more distant subpopulations (Watts et al 1990;Iacchei et al 2013;Thomas et al 2015;Norderhaug et al 2016;DiBattista et al 2017). Temporally, patterns of genotypic differentiation fluctuate through time because of turnover in genotypic variation (Johnson and Black 1982;Hogan et al 2010Hogan et al , 2012Jackson et al 2017). Consequently, genotypic differentiation within a focal site over time can be at comparable, or greater, magnitudes to that seen among subpopulations across space (Gould and Dunlap 2017;Villacorta-Rath et al 2017).…”
Section: Marine Connectivity and Chaotic Genetic Patchinessmentioning
confidence: 99%
“…However, my observations do not show strong support for true panmixia, and instead, show greater alignment with expectations of chaotic genetic patchiness (Table 3.1). Spatial genotypic structure was temporally variable and unrelated to the distance between sites (Figure 3.2), a typical feature of chaotic genetic patchiness (Johnson and Black 1982;DiBattista et al 2017;Jackson et al 2017).…”
Section: Chaotic Genetic Patchiness: the Genomic Background For Marinmentioning
confidence: 99%
See 2 more Smart Citations